A guide to Florida’s common bark and ambrosia beetles - Craig Bateman; Jiri Hulcr (EDIS)
This 36-page guide provides an introduction to the biology and identification of Florida’s bark and ambrosia beetles. Written by Craig Bateman and Jiri Hulcr, and published by the UF Department of School of Forest Resources and Conservation, September 2014.